Antioxidant and antitumor activity of nanoliposomes and solid nanoparticles loaded with rhenium-platinum system in rats with Guerin carcinoma - Shamelashvili , K.L. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Despite significant progress in recent decades in the development of chemotherapeutic agents with high efficacy and tolerability, cancer treatment often continues to be challenging due to adverse effects and drug resistance developed by tumor cells. These problems still call for research into new treatments that combine good efficacy and selectivity. Objective of the work was to investigate the effect of the administration of rhenium(III) cluster compounds on the intensity of lipid peroxidation (LPO), the activity of erythrocyte antioxidant protection enzymes superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GP) in a model of tumor growth (Herren’s carcinoma). Methods - experimental models of carcinogenesis (development of Geren’s carcinoma). Photocolorimetric methods - to determine the content of TBC-active products and the activity of antioxidant protection enzymes (catalase, superoxide dismutase, glutathione peroxidase) in the blood of rats. Results. Administration of Re tetraisobut alone in the form of nanoliposomes and solids was not effective in inhibiting the growth of Geren’s carcinoma, however, it led to a significant decrease in the intensity of LPO in the blood plasma compared to the group of tumor-bearing rats, group T8. The introduction of the Re-Pt system led not only to a significant inhibition of tumor growth, but also to a significant decrease (normalization) of the concentration of LPO products. Encapsulation of the Re-Pt system in one nanoliposome or in a solid nanoparticle did not lead to the loss of anticarcinogenic and antioxidant properties of its components. The introduction of the Rhenium-Platinum system and its components led to an increase in the activity of SOD of erythrocytes and a decrease in the activity of CAT in comparison with the control and an increase in the activity of SOD in comparison with the group of tumor-bearing rats. It should be noted that the introduction of Re tetraisobut did not lead to the activation of CAT in comparison with the control group. When the Re-Pt system was introduced separately and in the system, an increase in the activity of HP was observed compared to the T8 group. Conclusion. Therefore, the normalization of the redox state of erythrocytes under the influence of Re tetraisobut in different forms of administration can be explained both by the activation of SOD, as a result of which the concentration of superoxide anion decreases, and by the activation of HP, which leads to a decrease in the concentration of hydrogen peroxide.